Sistem Absensi Rapat Pegawai Berbasis Web Menggunakan SDLC dan Laravel 11 pada Kementerian Pendidikan Tinggi, Sains, dan Teknologi - Joshua Ngantung; Jay Sihotang (J-INTECH ( Journal of Information and Technology), 2026)
The rapid development of information technology has significantly transformed administrative practices within government institutions, encouraging the transition from conventional manual systems to integrated digital platforms. In many public sector environments, employee attendance is still recorded manually, which often results in inefficiencies, delays in data processing, and a higher risk of recording errors. This study aims to develop and implement a web-based employee attendance system at the Legal Bureau of the Ministry of Education, Research, and Technology using Laravel 11 as the development framework and applying the System Development Life Cycle (SDLC) method as a structured development approach. In addition to system development, this research also evaluates the system’s functional performance through Black Box testing to ensure that each module operates according to the specified requirements and supports reliable administrative attendance management. The SDLC framework guides the development process through systematic stages, including planning, requirements analysis, system design, implementation, and testing, ensuring that the resulting system meets organizational needs effectively. The proposed system incorporates essential features such as secure user authentication, digital signature integration, and automated real-time attendance data recapitulation to enhance administrative accuracy and control. The improvement in administrative efficiency was evaluated by comparing the developed system with the previous manual attendance method, where employee data were recorded on paper-based forms, often causing delays in data collection and additional operational costs. The findings indicate that the developed system improves administrative efficiency, reduces manual data entry errors, enhances data accuracy, and accelerates reporting processes, thereby supporting administrative modernization and more effective digital governance.